A robust search for lepton flavour violating axions at Mu3e - Simon Knapen; Kevin Langhoff; Toby Opferkuch; Diego Redigolo (Journal of High Energy Physics)
Abstract We propose a search at Mu3e for lepton flavor violating axion(-like) particles in μ → 3e + a decays. By requiring an additional e + e − pair from internal conversion, one can circumvent the calibration challenges which plague the μ → e + a channel for axions lighter than 20 MeV. Crucially, the corresponding reduction in signal rate is to a large extent compensated for by Mu3e’s ability to resolve highly collimated tracks. For phase I of Mu3e, we project a sensitivity to decay constants as high as 6 × 109 GeV which probes uncharted parameter space in scenarios of axion dark matter. The sensitivity to axions which couple primarily to right-handed leptons can be further improved by leveraging the polarisation of the muon beam.